2008
DOI: 10.1534/genetics.108.088591
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Pax6 Activity Levels to the Extent of Eye Development in the Mouse, Mus musculus

Abstract: In this study we extend the mouse Pax6 mutant allelic series to include a homozygous and hemizygous viable hypomorph allele. The Pax6 132-14Neu allele is a Phe272Ile missense mutation within the third helix of the homeodomain. The mutant Pax6 homeodomain shows greatly reduced binding activity to the P3 DNA binding target. Glucagon-promoter activation by the entire mutant Pax6 product of a reporter gene driven by the G1 paired and homeodomain DNA binding target was slightly increased. We constructed mutant Pax6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 66 publications
3
42
0
Order By: Relevance
“…Body weight and gross eye morphology: Eye morphology was assessed as previously described (Favor et al 2001(Favor et al , 2008. P35 heterozygous mutant and wild-type littermates were ophthalmologically examined by slit lamp microscopy and categorized for the degree of lens/corneal opacity and extreme microphthalmia.…”
Section: Methodsmentioning
confidence: 99%
“…Body weight and gross eye morphology: Eye morphology was assessed as previously described (Favor et al 2001(Favor et al , 2008. P35 heterozygous mutant and wild-type littermates were ophthalmologically examined by slit lamp microscopy and categorized for the degree of lens/corneal opacity and extreme microphthalmia.…”
Section: Methodsmentioning
confidence: 99%
“…Usually, the expressivity of heterozygous Pax6 mutations is variable, with individuals exhibiting a range of phenotypes from small anterior polar cataracts to the more visually significant anterior polar lens opacities, corneal adhesions, iris abnormalities and microphthalmia. Furthermore, the degree of phenotype expressed between the two eyes of the same person is variable ( [95] and references therein).…”
Section: Genes Causing Juvenile Cataractmentioning
confidence: 99%
“…It was further confirmed that the highly conserved Pax6 is a universal master control gene for eye development in the animal kingdom. Similar to the studied Pax6 genes in zebrafish 42 , Drosophila 36 , quail 43 , mouse [44][45][46] , and human 21,47,48 , the non-conserved C-terminus of the collembolan Pax6 is vital for protein transactivation ability. In our study, gradual deletions from the C-terminal end of collembolan Pax6 led to a gradual loss of activity in inducing ectopic eyes on Drosophila (Fig.…”
Section: Discussionmentioning
confidence: 88%